Impact of Frailty on Acute Rehabilitation Outcomes: An Observational Study in a Regional Australian Context. (3rd July 2022) - Andersen, Kate; Hewitt, Lyndel; Davis, Kimberley J.
Abstract: Aims: To determine associations between frailty and patient outcomes for participants in an acute rehabilitation program. Methods: Retrospective participant data (n = 987) was extracted, and correlations between the Clinical Frailty Scale (CFS) and patient outcomes (FIM TM, FIM TM Efficiency, LOS, Discharge Destination, Unexpected clinical complication) were examined through statistical analysis (Logistic regression, ANCOVA, Kendall's Tau, odds ratios). Results: The study cohort was 49.1% female and 50.9% male, averaging 82.3 years of age. FIM TM was weakly correlated with frailty, with both extent and efficiency declining with increasing frailty. This was statistically significant, despite being weak ( p < 0.001). There was a similar correlation between increasing CFS and less favorable discharge destination. CFS was not a reliable indicator of LOS nor unexpected clinical complication. Conclusions: More frail patients often benefited from rehabilitation, and frailty score alone should not be used to select acute rehabilitation inpatients.